Vascular Aging in Women: is Estrogen the Fountain of Youth? - Novella, Susana; Dantas, Ana Paula; Segarra, Gloria; Medina, Pascual; Hermenegildo, Carlos (Frontiers in Physiology, 2012)
Aging is a physiological process associated with structural and functional changes in vasculature, including endothelial dysfunction, arterial stiffening and remodeling, impaired angiogenesis, and defective vascular repair, and with an increasing prevalence of atherosclerosis. The risk of cardiovascular disease differs between men and women, remaining lower in women during their fertile years and reaching values similar to their male peers after menopause. Menopause is marked by the loss of endogenous estrogen production. Therefore, estrogens have been implicated in premenopausal protection from cardiovascular disease, an assumption supported by experimental and some clinical studies, where estrogen induces protective effects in vascular endothelium. Indeed, estradiol promotes endothelial vasodilator synthesis, including NO production through increased expression and activity of endothelial nitric oxide synthase, and modulates prostacyclin and thromboxane A2 release; the thromboxane A2 pathway plays a key role in regulating vascular tone in females in both normal and in pathophysiologic states. Contrary to experimental results, some clinical trials found no cardiovascular benefit from estrogen replacement therapy in aged postmenopausal women. These discrepancies could be due to the “Timing Hypothesis” which suggests that estrogen-mediated vascular benefits may occur only before the detrimental effects of aging are established in the vasculature. Thus, there is still a gap in the knowledge, understanding, and general awareness of mechanisms for cardiovascular aging in women. In this review, we discuss clinical and experimental data on the effects of aging, estrogens and hormonal replacement therapy on vascular function of females to delve into how menopause and aging contribute jointly to vascular aging and how estrogen modulates the vascular responses at different ages.